2018
DOI: 10.1056/nejmoa1801174
|View full text |Cite
|
Sign up to set email alerts
|

Alirocumab and Cardiovascular Outcomes after Acute Coronary Syndrome

Abstract: BACKGROUNDPatients who have had an acute coronary syndrome are at high risk for recurrent ischemic cardiovascular events. We sought to determine whether alirocumab, a human monoclonal antibody to proprotein convertase subtilisin-kexin type 9 (PCSK9), would improve cardiovascular outcomes after an acute coronary syndrome in patients receiving high-intensity statin therapy. METHODSWe conducted a multicenter, randomized, double-blind, placebo-controlled trial involving 18,924 patients who had an acute coronary sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

47
1,681
5
117

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 2,601 publications
(2,088 citation statements)
references
References 22 publications
47
1,681
5
117
Order By: Relevance
“…Monoclonal antibodies targeting PCSK9, namely alirocumab and evolocumab, have shown success in lowering LDL‐C and are currently approved for use in hypercholesterolemic patients who otherwise fail to respond to statin therapy . Thus, in the ODYSSEY OUTCOMES (Evaluation of Cardiovascular Outcomes After an Acute Coronary Syndrome During Treatment With Alirocumab) clinical trial of 18 924 participants, the risk of recurring cardiovascular events was reduced in patients with previous acute coronary syndrome who were on high intensity statin therapy when they received alirocumab compared to the placebo control . In the FOURIER (Further Cardiovascular Outcomes Research With PCSK9 Inhibition in Subjects With Elevated Risk) trial involving 27 564 participants with CVD and LDL‐C of 70 mg dL –1 (1.8 mmol L –1 ), evolocumab reduced both LDL‐C and the risk of cardiovascular events compared to those receiving placebo .…”
Section: Current Anti‐atherogenic Therapies Their Limitations and Tmentioning
confidence: 99%
“…Monoclonal antibodies targeting PCSK9, namely alirocumab and evolocumab, have shown success in lowering LDL‐C and are currently approved for use in hypercholesterolemic patients who otherwise fail to respond to statin therapy . Thus, in the ODYSSEY OUTCOMES (Evaluation of Cardiovascular Outcomes After an Acute Coronary Syndrome During Treatment With Alirocumab) clinical trial of 18 924 participants, the risk of recurring cardiovascular events was reduced in patients with previous acute coronary syndrome who were on high intensity statin therapy when they received alirocumab compared to the placebo control . In the FOURIER (Further Cardiovascular Outcomes Research With PCSK9 Inhibition in Subjects With Elevated Risk) trial involving 27 564 participants with CVD and LDL‐C of 70 mg dL –1 (1.8 mmol L –1 ), evolocumab reduced both LDL‐C and the risk of cardiovascular events compared to those receiving placebo .…”
Section: Current Anti‐atherogenic Therapies Their Limitations and Tmentioning
confidence: 99%
“…Sustained exposure to highly elevated LDL‐C levels accelerates cholesterol deposition and vascular inflammation with subsequent development of ASCVD progression and premature cardiovascular events . The evidence clearly indicates that reducing LDL‐C by statins, ezetimibe, or monoclonal antibodies for proprotein convertase subtilisin/kexin type 9 (PCSK9) inhibition can prevent ASCVD‐associated events . LDL‐C has both a causal and a cumulative effect on the risk of ASCVD.…”
Section: Introductionmentioning
confidence: 99%
“…Evolocumab and alirocumab, the two compounds that reached the market, were tested in full programs of phase III studies (PROFICIO and ODYSSEY, respectively) focusing on changes in the lipid profile and tolerability in candidates suitable for this type of medicine (i.e., high‐risk statin‐intolerant patients with primary hypercholesterolemia and patients with heterozygous FH inadequately controlled by standard therapy) ( Table 1 ). However, the two main cardiovascular outcome trials using anti–PCSK‐9 antibodies (FOURIER and ODYSSEY OUTCOMES, respectively) did not target these “challenging” patients but rather broad categories of high‐risk patients with LDL‐C levels perhaps not “optimal” but acceptably controlled through statins (baseline LDL‐C 92 mg/dL in FOURIER and 87 mg/dL in ODYSSEY OUTCOMES). These values are substantially lower than those of most studies with surrogate outcomes that provided backing to regulatory filing ( Table 1 ).…”
Section: Ldl Trialsmentioning
confidence: 99%
“…The meta‐regression scatter plot was constructed using the same data on statin trials published by Silverman et al . in 2016 (eFigure in the Supplemental Material of the quoted paper) with the addition of seven more recent studies with ezetimibe and PCSK‐9 inhibitors . Data of individual trials included in the analysis are shown in Table .…”
Section: Ldl Trialsmentioning
confidence: 99%